The Effect of Corporate Governance Elements on Audit Risk - Saeedi, Heidar; Rezazade, Javad; Sepasi, Sahar; Amri Asrami, Mohammad (Business, Marketing, and Finance Open, 2025)
The auditor’s opinion enhances the credibility of financial statements, enabling financial statement users to rely on them with greater confidence in their decision-making processes. The objective of this study is to examine the effect of corporate governance elements—including audit committee independence, board independence, CEO duality, ownership structure, and audit quality—on audit risk. The present research is applied in nature and follows an analytical approach. Data were collected from the financial statements of 105 companies listed on the Tehran Stock Exchange during the period 2015–2021. After testing the classical regression assumptions, a panel data regression model with fixed effects was employed to test the research hypotheses. The findings indicate a significant negative relationship between audit committee independence, board independence, audit quality, and institutional ownership with audit risk. However, a significant positive relationship was found between CEO duality and audit risk. Therefore, greater audit committee independence, higher board independence, a larger proportion of institutional ownership, and higher audit quality are associated with lower audit risk. Conversely, when the CEO simultaneously holds dual roles, such as serving as chairperson or vice-chairperson of the board, audit risk increases. The results of this study, by examining the impact of corporate governance elements on audit risk, can assist auditors in more effectively assessing audit risk.